The Effect Of Feeding Artificial and Natural Feeding (Azolla microphylla) On The Growth Rate Of Nila Fish (Oreochromis niloticus) - Muhammad, Fadhel; Surianti, Surianti; Putri, A Rini Sahni (Jurnal Sains dan Teknologi Perikanan, 2025)
Sidenreng Rappang Regency has great potential in the freshwater fisheries sector, especially in tilapia cultivation and is the main choice for local farmers because the Sidrap area is mostly land and has no coastline. The problem in this study is to determine the most effective type of feed in increasing the growth rate of tilapia. Therefore, the purpose of this study is to identify the best feed to maximize the growth of tilapia. This research was conducted in August-September 2024 at the Fisheries Science Development Pond, Muhammadiyah University of Sidenreng Rappang, Pancarijang District, Sidenreng Rappang Regency, South Sulawesi. The method used in this study is an experimental method with a Completely Randomized Design (CRD) experimental design. The experiment consisted of two treatments with two replications each, so that there were a total of six experimental units. The results of the analysis of variance showed that the provision of natural and artificial feed had a significant effect on the growth rate of tilapia (p <0.05). Further analysis using the W-Tukey test revealed differences between feed A and feed B. Based on the results of the study, it was found that fish fed commercial feed experienced the highest growth with an average of 7.53 ± 0.05, while the lowest growth was found in fish fed natural feed with an average of 5.36 ± 0.11. This shows that artificial feed is more effective in increasing the growth of tilapia because it has a more balanced nutritional content, especially in terms of protein and energy, which is in accordance with the metabolic needs of fish. However, natural feed can still be used to support the survival of tilapia.